Utilization of banana (Musa sapientum var. compressa) for the production of fries - Combong, Ma. Bonnah Fe Quemado (2008.)
Saba (Musa sapientum car. compressa) banana has potential for banana fries production as shown in this study.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana; Musa sapientum var. compressa; Banana fries